The impact of academic research: on character formation, ethical education, and the communication of values in late modern pluralistic societies - Schweiker, William; Witte, John; Welker, Michael; Pickard, Stephen K. (Evangelische Verlagsanstalt, 2021)
This volume addresses whether, how, and where academic research has an impact on ethical education, character formation, and the communication of values in late modern pluralistic societies. It reflects the great impacts of a global network of research universities, with the enormous range from the natural sciences to mathematics, historical and theological investigations. It offers praises of the institutionalized impact of the search for truth and the defense of tested truth-claims, but also skeptical voices with respect to the ethical impact of academic research today. With contributions by Stefan Alkier (Frankfurt), Rüdiger Bittner (Bielefeld), Celia Deane-Drummond (Oxford), Bernold Fiedler (Berlin), Andreas Glaeser (Chicago), Gary Hauck (Atlanta), Jörg Hüfner (Heidelberg), Michael Kirschfink (Heidelberg), Andreas Schüle (Leipzig), William Schweiker (Chicago), Michael Welker (Heidelberg), and John Witte, Jr. (Atlanta). [Der Einfluss der akademischen Forschung auf Charakterbildung, ethische Erziehung und Kommunikation von Werten in spätmodernen pluralistischen Gesellschaften] Dieser Band befasst sich mit der Frage, ob, wie und wo akademische Forschung Auswirkungen auf die ethische Bildung, die Charakterbildung und die Kommunikation von Werten in spätmodernen pluralistischen Gesellschaften hat. Es spiegelt die großen Auswirkungen eines globalen Netzwerks von Forschungsuniversitäten wider, mit einem enormen Spektrum von Naturwissenschaften über Mathematik bis hin zu historischen und theologischen Untersuchungen. Es lobt die institutionalisierten Auswirkungen der Suche nach der Wahrheit und die Verteidigung geprüfter Wahrheitsansprüche, aber auch skeptische Stimmen in Bezug auf die ethischen Auswirkungen der heutigen akademischen Forschung.